2002
DOI: 10.1002/eat.10038
|View full text |Cite
|
Sign up to set email alerts
|

Loss of control over eating, adiposity, and psychopathology in overweight children

Abstract: OBJECTIVE-To investigate the relationship between loss of control over eating, adiposity, and psychological distress in a non-treatment sample of overweight children.METHOD-Based on self-reports of eating episodes, 112 overweight children, 6-10 y, were categorized using the Questionnaire of Eating and Weight Patterns -Adolescent Version into those describing episodes of loss of control over eating (LC), and those with no loss of control (NoLC). Groups were compared on measures of adiposity, dieting and eating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
172
5
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(200 citation statements)
references
References 47 publications
15
172
5
5
Order By: Relevance
“…31,32 Moreover, using the same cutoffs for the CBCL as Epstein et al 6 and according to gender, between 41.4 and 53.1% of the youngsters seeking weight-loss treatment showed considerable adjustment problems, whereas their parents scored higher than a representative norm group on psychiatric symptoms. Compared with the study of Epstein et al, 6 the present study even found a larger percentage of parents exceeding clinical cutoffs for psychiatric symptoms (59.6% of mothers and 35.7% of fathers) than Epstein et al 6 (27.6% of mothers).…”
Section: Parent Characteristics and Psychopathology In Obesity V Decamentioning
confidence: 93%
“…31,32 Moreover, using the same cutoffs for the CBCL as Epstein et al 6 and according to gender, between 41.4 and 53.1% of the youngsters seeking weight-loss treatment showed considerable adjustment problems, whereas their parents scored higher than a representative norm group on psychiatric symptoms. Compared with the study of Epstein et al, 6 the present study even found a larger percentage of parents exceeding clinical cutoffs for psychiatric symptoms (59.6% of mothers and 35.7% of fathers) than Epstein et al 6 (27.6% of mothers).…”
Section: Parent Characteristics and Psychopathology In Obesity V Decamentioning
confidence: 93%
“…Some studies use queries to further explain loss of control (e.g., ''when you start to eat, and you eat and eat and eat, and you just can't stop''). 12 Other batteries including the Questionnaire of Eating and Weight Patterns-Adolescent version (QEWP-A) 9,12-15 and the Binge Eating Scale (BES) 16 have also been used; however, these measures were not designed to be interviewer-administered. It has been reported that self-report measures of eating disorder assessment in children (e.g.…”
Section: Assessment Of Bed In Childrenmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] For example, when using the ChEDE, studies have found a 0% prevalence of BED 22,23 ; however, 7.9% of children aged 10-16 seeking outpatient weight loss treatment reported subthreshold binge eating 22 and of children aged 6-14, 6.2%, 3.1%, and 20.4% reported objective binge episodes, subjective binge episodes, and overeating, respectively. 23 When using the QEWP-A, although only 5.3% of children aged 6-10 met BED criteria, 33.1% reported loss of control over eating.…”
Section: Prevalence Of Bed In Childrenmentioning
confidence: 99%
See 2 more Smart Citations